If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9x + 2) = 6x(4 + -5) + -5 Reorder the terms: 3(2 + 9x) = 6x(4 + -5) + -5 (2 * 3 + 9x * 3) = 6x(4 + -5) + -5 (6 + 27x) = 6x(4 + -5) + -5 Combine like terms: 4 + -5 = -1 6 + 27x = 6x(-1) + -5 Reorder the terms for easier multiplication: 6 + 27x = 6 * -1x + -5 Multiply 6 * -1 6 + 27x = -6x + -5 Reorder the terms: 6 + 27x = -5 + -6x Solving 6 + 27x = -5 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 6 + 27x + 6x = -5 + -6x + 6x Combine like terms: 27x + 6x = 33x 6 + 33x = -5 + -6x + 6x Combine like terms: -6x + 6x = 0 6 + 33x = -5 + 0 6 + 33x = -5 Add '-6' to each side of the equation. 6 + -6 + 33x = -5 + -6 Combine like terms: 6 + -6 = 0 0 + 33x = -5 + -6 33x = -5 + -6 Combine like terms: -5 + -6 = -11 33x = -11 Divide each side by '33'. x = -0.3333333333 Simplifying x = -0.3333333333
| 9x+5=4k(x-2)+8 | | 30x-12x^2=0 | | x+y=8y=x+6 | | 6+55x=44x+7x | | sqrt(3)cos^2x=2cosx | | 4x+2+y-2xy=0 | | 6n-9=27 | | 1-2cos^2x=0 | | 1-2cos^2x=1 | | (9x-7w)(4x+6y)(3y+3w)= | | 32(x)=0.25 | | (8x+3y+67)=73 | | ax=a+x | | -27+2= | | 7(10x+2)=2x(30-5) | | 7(10x+14)=2x(30-5) | | =sin^3(25) | | 8(0.25+d)-8d=2 | | 9c-8d=5 | | 8c-8d=2 | | v=w+-4x | | 2(4x+3)-(3x)=-6 | | 3*(11*(x+2)-2*(2-5x))=2*(8*(3+4x)+5)-(6x+11) | | 3x+16=2x+26 | | x^2+16=y | | 3(x+5)=11-x | | 9x-6w-4y+3w+3+9y= | | 8-3c+9-6-4c+2d-d= | | 49x+7=8*7x | | 3*(2*(x+4)-3*(x-5))=4*(3*(x+2)-4(x+1))+15 | | b+1b+1b+1b+1= | | 18+x=-x-1 |